P218 Safetxt: a randomised controlled trial of an intervention delivered by mobile phone messaging designed to reduce infection with chlamydia and gonorrhoea- recruitment methods. (8th June 2017) - Free, Caroline; Swinson, Rebecca; Potter, Kimberley; McCarthy, Ona; Knight, Rosemary; Baraitser, Paula; Hickson, Ford; French, Rebecca; Michie, Susan; Wellings, Kaye; Palmer, Melissa; Bailey, Julia
Abstract : Introduction: Trial recruitment is one of the most important trial tasks as full recruitment provides trials with sufficient power to detect intervention effects. Yet, two thirds of randomised controlled trials fail to fully recruit. The NIHR safetxt trial is a single blind randomised controlled trial to evaluate the effect of a safer sex intervention delivered by text message on Chlamydia and Gonorrhoea infection at 12 months. 5000 people aged 16–24 are being recruited from UK GU and Sexual and Reproductive Health services. We describe the methods used to facilitate recruitment. Methods: Mixed methods informed by evidence from behavioural science including: monitoring recruitment, feedback, rewards, identifying barriers to recruitment, shared learning between recruiting clinics and staff, development of materials to address barriers to recruitment and evaluation of materials developed. Results: 34 GU and Sexual and Reproductive Health Services across the UK are involved in the recruitment endeavour. A further 13 sites are due to start recruitment. Over 1100 participants have been recruited, ahead of current recruitment targets. Telephone and face-to-face meetings with staff in recruiting services generated ideas to increase recruitment, enabled services new to trial recruitment or research nurses new to Sexual Health to learn from experienced recruiters, facilitated mutual learning and resulted in the development of materials to support staff in recruitment. Discussion: The safetxt trial is recruiting ahead of schedule. It will be a major achievement if the safetxt collaboration between GU and Sexual and Reproductive Health services and the trial management team recruit 5000 participants on time.